ESG Integration In SOEs: Transformation of Environmental Protection and Embodiment of Sustainable Business in SOEs - Diva Nur Amartha Suci; Meliaila, Aurora Jillena (Unram Law Review, 2024)
Climate change carries enormous risks and threatens the lives of many people. Environmental damage not only endangers living creatures, but risks causing business losses. Therefore, there is a demand from the public and investors to publish sustainability reports. The disclosure of a sustainable report not only acts as a tool to maintain reputation, but also as a form of evaluation of business activities that have been carried out in a certain period of time. Apart from that, sustainability principles are not only used as a reporting reference, but are also used as a consideration in making business and investment decisions. As a member country of the UNFCCC, Indonesia has a target to contribute to overcoming climate change. State-Owned Enterprises, which are large state-owned business conglomerations, should integrate ESG aspects as a consideration for their business operations. As mandated by Article 33 of the Constitution of the Republic of Indonesia, SOEs have control over businesses in sectors that cover the lives of many people. Through Glasgow COP26, IFRS has published ISSB as a reference in forming sustainability reports. This is a response to the systematic misalignment of sustainability reporting that exists throughout the world. Therefore, an international standardization is needed which can be used as a reference. In this case, SOEs should adopt these international standards in connection with the absence of regulations that specifically regulate the obligation for SOEs to carry out environmental considerations. This article aimed to discuss the regulatory status quo that applies in the context of implementing ESG and how ESG will later be integrated as a form of realizing sustainable business.